Synchronous mucinous metaplasia and neoplasia of the female genital tract with both pulmonary metastases and STK11/KRAS gene mutations: a case report - Wang, Ru; Yu, Hao; Liu, Ming; Hao, Ting; Wang, Xiangyu; Cao, Lianbao (Frontiers in Oncology, 2023)
Multiple morphological changes in two or more sites of concurrent multifocal mucinous lesions in the female genital tract are indicative of SMMN-FGT, which is unrelated to high-risk HPV infection. MUC6 and HIK-1083 showed positive characteristic immunohistochemistry. Seldom is the condition described. Here we describe an SMMN-FGT patient who also had lung metastases and STK11/KRAS gene mutations. Based on the current researches, we hypothesize that SMMN-FGT is closely associated with the development of cervical gastric adenocarcinoma.